REASON, PASSION AND SELF-CONTROL: UNDERSTANDING THE MORAL BASIS OF THE PROVOCATION DEFENCE - Mousourakis, George (Revue de droit de l'Université de Sherbrooke, 2007)
This paper discusses the nature of provocation and the proper way to interpret provocation as a defence, particularly in relation to murder charges. Its aim is to explain how provocation can be conceptualized as a partial excuse by examining the traditional understanding of the provocation defence as a concession to human frailty. It is argued that the defence operates as an excuse on the assumption that an act of provocation is capable of raising in a person such a degree of psychological pressure, in the form of angry passion, as to deprive her of her ability to act morally voluntarily, i.e. the ability to act according to an all-things-considered moral choice. The paper aims to explain, moreover, why provocation cannot provide a complete excuse. It is argued that, while the provoked agent may not be able to suppress her anger, she is deemed capable of recognizing that there are overriding reasons for not acting on the desire to kill which may arise in her emotional state. Although a successful plea of provocation negates the degree of moral culpability required for murder, it cannot prevent conviction for the lesser offence of manslaughter for a provoked killing still manifests a socially undesirable disposition or trait of character.